Political Blogs As An Educational Tool In Learning Arabic: Opportunities And Challenges - Ahmed Muhamed Wafiq Othman; Lily Hanefarezan Binti Asbulah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study examines the effectiveness of political blogs as instructional resources in teaching Arabic to non-native speakers, situating the analysis within communicative and critical literacy approaches to language learning. It explores both the pedagogical opportunities these blogs offer for developing advanced language skills and the linguistic, cultural, and ideological challenges associated with their integration into the classroom. Adopting a mixed-methods research design, the study combines quantitative and qualitative data to provide a comprehensive evaluation of this emerging pedagogical practice. Data were collected through a content analysis of a purposive sample of thirty (30) Arabic political blogs representing diverse ideological orientations and regional contexts. In addition, an online questionnaire and semi-structured interviews were administered to one hundred and twenty (120) intermediate- and advanced-level learners of Arabic from varied linguistic and cultural backgrounds. To measure learning outcomes, pre- and post-tests were conducted with a subgroup of forty (40) learners who engaged with political blogs as supplementary instructional materials over twelve weeks. Quantitative data were analyzed using descriptive and inferential statistical techniques via SPSS. In contrast, qualitative data were examined through thematic coding and critical discourse analysis to identify salient linguistic, stylistic, and discursive features. The findings reveal statistically significant gains in learners’ acquisition of specialized political vocabulary, reading comprehension, and academic writing skills, alongside increased political and cultural awareness. However, the study also highlights persistent challenges, including the complexity of political discourse, ideological bias, and the diglossic gap between Modern Standard Arabic and colloquial varieties. The study concludes that the pedagogically guided integration of political blogs—supported by careful content selection, scaffolded tasks, and explicit training in critical discourse analysis—can effectively enhance advanced Arabic language learning while mitigating potential linguistic and ideological constraints.